2019
DOI: 10.1016/j.celrep.2019.09.087
|View full text |Cite
|
Sign up to set email alerts
|

NFE2L3 Controls Colon Cancer Cell Growth through Regulation of DUX4, a CDK1 Inhibitor

Abstract: Constitutive nuclear factor kB (NF-kB) activation is a hallmark of colon tumor growth. Cyclin-dependent kinases (CDKs) are critical cell-cycle regulators, and inhibition of CDK activity has been used successfully as anticancer therapy. Here, we show that the NFE2L3 transcription factor functions as a key regulator in a pathway that links NF-kB signaling to the control of CDK1 activity, thereby driving colon cancer cell proliferation. We found that NFE2L3 expression is regulated by the RELA subunit of NF-kB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 68 publications
(67 reference statements)
2
58
1
Order By: Relevance
“…Several studies have reported that decreased NFE2L3 expression inhibits proliferation of cells 15 , 18 . To investigate the potential effect of NFE2L3 on HepG2 cell proliferation, NFE2L3 shRNA interference lentiviral vector was performed to knockdown NFE2L3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that decreased NFE2L3 expression inhibits proliferation of cells 15 , 18 . To investigate the potential effect of NFE2L3 on HepG2 cell proliferation, NFE2L3 shRNA interference lentiviral vector was performed to knockdown NFE2L3.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the above results, the expression of CDK2 and PCNA also decreased, it is further confirmed that NFE2L3 plays an important role in cell growth and proliferation. Cyclin D1 is a key mediator of cell growth and proliferation, some researches had proved that NFE2L3 regulated the expression of cyclin D1 in CRC while another article pointed out that the silencing of NFE2L3 will increase the level of DUX4, a direct inhibitor of CDK1, and reduce the proliferation and tumorigenicity of colon cancer cells 15 , 18 . In addition, both cytoplasmic and nuclear β-catenin were decreased by knockdown NFE2L3, indicating NFE2L3 significantly regulated transcription of β-catenin in liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We guess another biological meaning of our findings in cancer. The functional difference between NRF3 and NRF1 is not in the regulation of the proteasome activity rather in the expression of cancer-related genes such as VEGFA and DUX4 that other groups have recently identified as NRF3-specific target genes 19,20 . Meanwhile, cancer cells have to keep NRF1 as a backup for proteasome regulation, because the proteasome activity is crucial for more rapid proliferation of cancer cells 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Xue et al [37] reported that the activity of CDK1 is highly elevated in CRC tissues compared to noncancerous tissues, and it predicts distant metastasis risk in CRC; CDK1 can promote the progression of CRC through phosphorylation of JAK1 to activate the JAK/ STAT3 signaling pathway. Bury et al [38] indicated that high gene expression levels of CDK1 stimulated the proliferation and migration of colorectal cancer cells, and inhibition of CDK1 activity by using inhibitors can inhibit the proliferation of colorectal cancer cells in vitro and in vivo. In addition, Zhang et al [39] indicated that frequent overexpression of CDK1 in human CRCs is associated with the therapeutic target, and the therapeutic resistance of BRAF mutant human CRC can be suppressed by targeting CDK1.…”
Section: Mki67mentioning
confidence: 99%